From phenotypes to causal sequences: using genome wide association studies to dissect the sequence basis for variation of plant development. (February 2015) - Ogura, Takehiko; Busch, Wolfgang
Highlights: Genome Wide Association Studies (GWASs) have been conducted in 22 plant species. GWASs have uncovered novel mechanisms and genes underlying variation of growth and development. GWASs frequently identify different sets of genes than those identified by mutant screening. Phenotypic data for GWAS can be used to comprehend correlations and mechanistic links between traits. Experimental design, conduct and analysis are keys for successful GWASs. Abstract : Tremendous natural variation of growth and development exists within species. Uncovering the molecular mechanisms that tune growth and development promises to shed light on a broad set of biological issues including genotype to phenotype relations, regulatory mechanisms of biological processes and evolutionary questions. Recent progress in sequencing and data processing capabilities has enabled Genome Wide Association Studies (GWASs) to identify DNA sequence polymorphisms that underlie the variation of biological traits. In the last years, GWASs have proven powerful in revealing the complex genetic bases of many phenotypes in various plant species. Here we highlight successful recent GWASs that uncovered mechanistic and sequence bases of trait variation related to plant growth and development and discuss important considerations for conducting successful GWASs.